The Influence of Islamic Business Ethics on Consumer Satisfaction on the Shoppe Platform - juned el; Irfan Fuadi; Hikam Moh (Universitas Nurul Jadid, 2025)
This study aims to analyze the influence of Islamic business ethics on consumer satisfaction on the Shopee e-commerce platform. Islamic business ethics, based on values such as justice, honesty, trust, and responsibility, are believed to enhance consumer satisfaction in online transactions. The research employs a quantitative approach using an explanatory survey method and involves 100 Shopee users selected through purposive random sampling. Data were collected through an online questionnaire using a Likert scale and analyzed with multiple linear regression. The results show that Islamic business ethics have a significant influence on consumer satisfaction, both partially and simultaneously. This study contributes to understanding the importance of applying Islamic ethical values in digital business practices to build consumer trust and loyalty.